INVESTIGATION INTO THE IMPACT OF CARVCROL EXTRACTS ON BACTERIA ISOLATES FROM OSTEOMYLITIS AFTER SURGERY - Tamara Ziyad Tariq; Saba Abdul Salam Hamid Al-Sultan; Aws Ibrahim Sulaiman (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Carvacrol is one of the most ancient medicinal herbs. Carvacrol contains different alkaloids, flavonoids and saponins. In present studies the antimicrobial activity of Carvacrol alcoholic extract against Gram-negative bacterial and Gram-positive bacterial were determined by the microtiter plate method. Gram-negative bacterial and Gram-positive bacterial strains isolated from osteomyelitis patients after surgery in Mosul city , A total of 60 samples were collected from various sources in Mosul hospitals, during the period from January 10, 2024 , to May 1, 2024. The Aim of this study is determining the effectiveness and effect of alcoholic extract of carvacrol on bacterial isolates taken from a Osteomyelitis after surgery. Bacterial culture results on blood agar, MacConkey agar and nutreint agar revealed 54 positive samples for bacterial growth. Among these, Staphylococcus aureus 22 isolates (32.8%), Pseudomonas aeruginosa 12 isolates (17.9%), Enterobacter cloacae 5 isolates (7.5%) Klebsiella pneumoniae 4 isolates (5.9%), Escherichia coli 4 isolates (5.9%), Proteus mirabilis 3 isolates (4.5%), Streptococcus viridans 3 isolates (4.5%), Corynebacterium spp 2 isolates (3%). As for the following bacterial isolates, each of them constituted one isolate out of a total of 67 isolates, at a rate of 1.5% for each: Providencia spp. , Acinetobacter spp., Staphylococcus saprophyticus , Klebsiella oxytoca , Enterococcus spp. , Enterococcus faecium , Citrobacter freundii , Streptococcus groups C , Bacillus cereus , Enterobacter spp. , Acinetobacter baumannii , Morganella morganii, using vitek-2. High-performance liquid chromatography (HPLC) analysis of Oregano plant revealed the presence of active compounds such as Carvacrol, thymol. Plant extracts from carvacrol demonstrated a substantial inhibitory effect. Results: study indicated that plant extracts exhibited higher inhibition than antibiotics. The minimum inhibitory concentration (MIC) while the results of the lowest inhibitory concentration of carvacrol for the bacterial species under study showed that it had an effect at a concentration of 615 µg/ml against Escherichia coli, 307.5 µg/ml for the species Corynebacterium stratium, Morganella morganii and Pseudomonas aeruginosa, and the least effect was 76.875 µg/ml on Staphylococcus aureus, it gave less results than the antibiotic used Carvacrol (Absorbance was measured at Wavelength 600) .